Pengaruh Self Assessment System, Pemahaman Perpajakan, Tarif Pajak Dan Kemungkinan Terdeteksi Kecurangan Terhadap Tindakan Tax Evasion - Muhammad Irsan; Surya Sanjaya; Khairul Anwar Pulungan (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The aim of this research is to determine the influence of the self-assessment system, understanding of taxation, tax rates and the possibility of detecting fraud either partially or simultaneously on tax evasion. Self-assessment system, understanding of taxation, tax rates and the possibility of detecting fraud in this research are used as independent variables and tax evasion measures are used as dependent variables. The research approach used in this research is an associative approach. The associative approach is a research approach that aims to determine the relationship between two or more variables in order to determine the relationship or influence between one variable and another variable. The population in this research is all individual taxpayers registered at KPP Pratama Medan Polonia, namely 168,335 taxpayers, while the sample taken was 100 taxpayers. Based on the results of hypothesis testing using the t test and f test, the results of the research are that understanding taxation and the possibility of detecting fraud have a significant effect on tax evasion actions. Meanwhile, the self-assessment system and tax rates do not have a significant effect on tax evasion actions. Based on the results of the f test, the results show that all independent variables in this study have a simultaneous influence on the tax evasion action.